Decitabine Induced Delayed Cardiomyopathy in Hematologic Malignancy. (30th September 2018) - Agasthi, Pradyumna; Narayanasamy, Hemalatha; Sorajja, Dan; Slack, James; Mookadam, Farouk
Abstract : Decitabine is a pyrimidine analogue of nucleoside cytidine, used for the treatment of myelodysplastic syndromes, chronic myelogenous leukemia, and acute myelogenous leukemia. We present a case of cardiomyopathy associated with decitabine used for secondary acute myelogenous leukemia. The patient presented with new heart failure symptoms and an ejection fraction decline.